THE DEVELOPMENT OF ENGLISH GRAMMAR MATERIAL FOR AUDITORY LEARNERS BASED ON YOUTUBE VIDEO - Wahyudi, Imam (Kurikula : Jurnal Pendidikan, 2024)
The primary objective of this study was to create suitable English grammar resources tailored for auditory learners by utilizing YouTube videos. This development was targeted at first-semester students enrolled in the Islamic Elementary School Education Program at the Tarbiyah Faculty of Institut Agama Islam Ngawi. The researcher employed the Research and Development (R&D) method, specifically the Thiagarajan Model, which involves four key phases: Analysis, Design, Development, and Implementation. Conducted within the Islamic Elementary School Education Program at the Tarbiyah Faculty of Institut Agama Islam Ngawi, this study involved 8 students characterized by an auditory learning style. The findings of this research indicated the appropriateness of the English grammar material designed for auditory learners and based on YouTube videos. Expert evaluations rated the material expert at 4, the language expert at 4, and the media/IT expert at 4, resulting in an overall mean score for product validity of 4, denoting an excellent rating. Consequently, it can be inferred that YouTube videos present an effective alternative teaching medium for auditory learners.